Peran Oksigen Terlarut terhadap Kualitas Air dan Sistem Drainase Berkelanjutan di Sungai Krueng Cunda, Lhokseumawe - Lusyana Eka Wardani; *Aisyah Protonia Tanjung (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Dissolved oxygen (DO) is a key indicator of water quality that critically determines the health of aquatic ecosystems and the effectiveness of natural water treatment processes. This study analyzes the role of DO in supporting sustainable drainage systems (SuDS) in the Krueng Cunda River, Lhokseumawe City, through a literature review and water quality analysis based on purposive sampling at five observation points. The analyzed parameters include temperature (29–33?°C), DO (6.3–7.7?mg/L), organic carbon (0.126–3.73%), pH (7.30–7.90), and total nitrogen (1.4–3.6?mg/L), compared with water quality standards according to Government Regulation No. 82 of 2001. The results show that DO levels in the Krueng Cunda River are within a good range (6.3–7.7?mg/L), corresponding to Class I–II, thus still supporting aquatic life and aerobic decomposition of organic matter. However, anthropogenic pressures from domestic activities and brackish aquaculture have the potential to reduce DO if not controlled through pollutant load management and enhancement of natural aeration. These findings highlight that the development of SuDS in the Krueng Cunda River should prioritize controlling organic pollution and designing drainage elements that promote aeration and the river’s self-purification processes.